A comparative study of the cooling-rate effect on rock strength reduction after microwave irradiation. (18th September 2020) - Micallef, Daniel; Rafezi, Hamed; Deyab, Samir M.; Hassani, Ferri; Ghoreishi-Madiseh, Seyed Ali
Abstract: A variety of machines are currently being used for mechanical excavation in mining and civil industries. A series of research works have been conducted at McGill University in the past decade to study the effects of microwave (MW) irradiation on rock mechanical properties. The idea is to enhance the excavation performance by improving the rate of penetration and decreasing the wear rate on the cutting tools. These two effects would eventually translate into economic benefits for mine operators. The effectiveness of MW on weakening rocks is proven, however the most efficient method to employ MW in mines is still under investigation. This article presents some experimental results on the effects of cooling- rate on rock strength. Brazilian Tensile Strength (BTS) of microwave treated samples were compared in natural air-cooled and water rapid-cooled conditions.